Stinetinglers ebook Stinetinglers series, book 1. - Stine, R. L. (Stinetinglers, 2022)
From New York Times bestselling author R.L. Stine, the master of horror for young readers, comes ten new stories that are sure to leave you shivering. A boy who hates bugs starts to see them everywhere. A basketball player's skin starts to almost drip off his hands—but no one else can see it. Three friends find a hole in the ground that just gets bigger, and bigger, and bigger... And each story is introduced by Stine himself, providing a personal touch sure to delight fans. Laced with Stine's signature humor and a hefty dose of nightmarish fun, Stinetinglers is perfect for fans of Scary Stories to Tell in the Dark and Stine's own Goosebumps books. These chilling tales prove that Stine's epic legacy in the horror genre is justly earned. Dive in, and beware: you might be sleeping with the lights on tonight!